Effects of Thyrotoxicosis on the Structure of Salivary Glands (Submandibular Glands) in Swiss Albino Mice (Mus musculus) - Alkasiy, K. S.; Al-Habib, M.F.; Sabrei, D. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The goal of this study was intend to study the effects of induced thyrotoxicosis on the histological structure of submandibular gland. Two groups of mature albino mice wen: used, the first group was injected (subcutaneous) daily with (0.2_0.4)ml norma] salinfor 11 days and used as control group, while the second group was injected daily wi th L_thyroxin (T4) 0.2mg /Kg (subcutaneous) for l l days. At the end of the treatment , supmandibular glands were processed for light microscopic examination . The result.s have shown the presence of degenertaive changes of major submandibular acini cells in animal treated with thyroxin with diminishing amounts of connective tissuelements . Beside these change infiltration with inflammatory cells were observed . From this study we can conclude that there is a relationship between thyroid gland and submandibular gland . Which might regulated the secretory activity of saliva .